INCREASING LITERACY COMPETENCE WITH A READING CORNER - Yen Aryni; Lis Supiatman; Micael Olivan Siahaan; Devi Manda Sari; Ravli Akbar Nasution (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
Abstract: Research indicates that establishing a Reading Corner in kindergarten significantly improves children's early literacy skills, including letter recognition, vocabulary growth, narrative understanding, and reading motivation. The study utilized a mixed-methods approach, combining quantitative pre-test and post-test analysis with qualitative classroom observations and teacher interviews. Quantitative results demonstrated that the experimental group using the Reading Corner showed statistically significant improvements in literacy compared to a control group (p < 0.05). The qualitative findings revealed increased student engagement, motivation to read, and enhanced oral language development. Themes of this study suggest that a literacy-rich environment fosters better reading habits and skills, aligning with contemporary pedagogical approaches emphasizing the importance of accessible reading resources for young learners. Thus, the Reading Corner is identified as a crucial tool in promoting foundational literacy among kindergarten students. Keywords: Literacy, Children, Reading Corner Abstrak: Penelitian menunjukkan bahwa pembentukan Pojok Baca di taman kanak-kanak secara signifikan meningkatkan keterampilan literasi awal anak-anak, termasuk pengenalan huruf, pertumbuhan kosakata, pemahaman naratif, dan motivasi membaca. Studi ini menggunakan pendekatan metode campuran, menggabungkan analisis kuantitatif pra-tes dan pasca-tes dengan observasi kelas kualitatif dan wawancara guru. Hasil kuantitatif menunjukkan bahwa kelompok eksperimen yang menggunakan Pojok Baca menunjukkan peningkatan literasi yang signifikan secara statistik dibandingkan dengan kelompok kontrol (p < 0,05). Temuan kualitatif mengungkapkan peningkatan keterlibatan siswa, motivasi untuk membaca, dan peningkatan perkembangan bahasa lisan. Tema studi ini menunjukkan bahwa lingkungan yang kaya literasi mendorong kebiasaan dan keterampilan membaca yang lebih baik, sejalan dengan pendekatan pedagogis kontemporer yang menekankan pentingnya sumber bacaan yang mudah diakses untuk anak-anak usia dini. Dengan demikian, Pojok Baca diidentifikasi sebagai alat penting dalam mempromosikan literasi dasar di kalangan siswa taman kanak-kanak. Kata Kunci: Literasi, Anak-anak, Pojok Baca